6‐3: Quantum Dot LEDs: Problems & Prospects. Issue 1 (May 2017) - Titov, Alexandre; Acharya, Krishna; Wang, Chenggong; Hyvonen, Jake; Tokarz, Jean; Holloway, Paul H.
Abstract : Colloidal quantum‐dot hybrid light‐emitting diodes (QLEDs) have been demonstrated that exhibit external quantum efficiencies >12% for all three colors (21% from green), both positive and negative ageing, and good charge injection. The role of nanoparticles in QLED charge injection was illustrated.